(untitled) (Journal of Engineering, 2024)
This study aims to study and evaluate the surface water use of Al-Shuwaija marsh by estimating the maximum value of water flow and the volume of water revenues through the hydrological analysis of the characteristics of these marsh basins in addition to the physical analysis of the characteristics of the selected design storm. The hydrological model was created for the watersheds of the Al-Shuwaija marsh. Sixty simulations were conducted to model the Shuwaija marsh for different return periods and rainstorms, where the model was calibrated and then validated to predict the flow and volume of water using the (WMS) program. The SCS method was used to calculate the value of the total curve number (CN) based on the land use and soil type of Al-Shuwaija marsh basins, where its value was 80.84. It has been shown via modelling that a discharge may be achieved into 8298 /sec at a return period of 100 years and obtain a discharge of up to 1775 /sec at a return period of 2 years. Based on the expected amount of precipitation that would fill the selected reservoir, three scenarios were assumed each scenario representing the area of the reservoir and the volume of incoming water.